Variations on The Concentration and Purity of Oil Palm Flowers (Elais guineensis Jac.) in Some Extraction Methods for Identification of the Flowering Gene - Winda Nawfetrias; Yuda Purwana Roswanjaya (Agrotech Journal, 2021)
Palm oil production is related to the number of fruit and is thought to be determined since the beginning of the flowering phase as the initial stage of fruit formation. Identification of oil palm flowing genes needs to be done as the first step of knowing the mechanism of flowering in oil palm molecular. Oil male and palm females contain high polysaccharides and polyphenolic compounds so they can inhibit the process of molecular identification. Molecular studies provide accurate and fast information about the potential of oil palm genetics as a commercial commercial commodity. The purity and concentration of DNA and the temperature of annealing are the main requirements for PCR-based molecular studies. The purpose of this study obtained the extraction method of oil palm flowers which produced high DNA concentration and purity and optimized the temperature of annealing to identify the flowering gene. DNA from male flower spike and female flowers is extracted using the A (SDS) method, method B (CTAB), method C (CTAB + PVP), and method D (commercial kit). Primary BMS annealing temperature for amplification of optimized flowering genes using PCR gradients. The extraction of male flowers and female flowers using the C (CTAB + PVP) method produces the best DNA concentration and purity compared to other methods. The best annealing temperature for male flower DNA amplification and female flowers using the BMS primer is 61.1 o C. Amplification of male flowers and female flowers using Primary BMS produces 1200 PB products. The results of DNA extraction and PCR amplification using the BMS primers in female flower samples are better than male flowers